Percussion : drumming, beating, striking - Mowitt, John, 1952- (Duke backfile, 2002)
By emphasizing the specifically percussive articulation of rhythm, this study contributes to the elaboration of critical musicology by both challenging its construction of music as essentially harmonic and by extending the interpretive vocabulary of music.